Formulation and Evaluation of Herbal Syrup - Mohan J, Devkar; Shahrukh S. M, Shaikh Shahrukh S. M; G. Jadhao, Amol; Jayshri Sanap, Miss.; A. Patil, Prashant (Asian Journal of Pharmaceutical Research and Development, 2021)
The cough it is a most common problem are face by the all people. There are two types of cough one is the Dry cough and second is wet cough. The dry cough is a no mucous and secretion while in wet cough there is cough mucous or secretion. The syrup is most commonly used and popular dosage form there is used in cure the cough and cold because it having ease of patients compliance. The herbal cough syrup was formulated using crude drugs as Pudina&Tulsi or Cinnamon as a main ingredient along with Honey. Today syrup is used for treatment of May ailments and to overcome symptoms of disease. The antioxidant syrup is used to treatment the cancer because of many stress condition and other oxidative reaction in body the free radical are generated by using theses, syrup the condition is overcome. Formulation at laboratory scale was done and evaluate for number of parameters such as PH, viscosity, Density, stability testing during evaluation formulation found to be stable and ready to use in a cough treatment.It is found that Antitussive activity produced by the Herbal formulation in the minimum dose was much better than the standard drug.